An engineered probiotic secreting Sj16 ameliorates colitis via Ruminococcaceae/butyrate/retinoic acid axis - Lifu Wang; Yao Liao; Ruibing Yang; Zifeng Zhu; Lichao Zhang; Zhongdao Wu; Xi Sun (Wiley, 2021)
Abstract Most inflammatory bowel disease (IBD) patients are unable to maintain a lifelong remission. Developing a novel therapeutic strategy is urgently needed. In this study, we adopt a new strategy to attenuate colitis using the Escherichia coli Nissle 1917 probiotic strain to express a schistosome immunoregulatory protein (Sj16) in the gastrointestinal tract. The genetically engineered Nissle 1917 (EcN‐Sj16) highly expressed Sj16 in the gastrointestinal tracts of dextran sulfate sodium‐induced colitis mice and significantly attenuated the clinical activity of colitis mice. Mechanistically, EcN‐Sj16 increased the intestinal microbiota diversity and selectively promoted the growth of Ruminococcaceae and therefore enhanced the butyrate production. Butyrate induced the expression of retinoic acid, which further attenuated the clinical activity of colitis mice by increasing Treg cells and decreasing Th17. Strikingly, retinoic acid inhibitor inhibited the therapeutic effects of EcN‐Sj16 in colitis mice. These findings suggest that EcN‐Sj16 represents a novel engineered probiotic that may be used to treat IBD.